Strategi Pemerintah dalam Meningkatkan Kualitas Pelayanan Publik di Kelurahan Karanganyar Kecamatan Astana Anyar Kota Bandung: Government Strategy in Improving the Quality of Public Services in Karanganyar Village, Astana Anyar District, Bandung City - Fajarwati , Neri (Puslatbang KHAN, 2023)
In general, the apparatus provides services to the community according to the needs of the community itself. However, the facts on the ground are that government officials have not been able to carry out their duties and functions properly. In addition to the quality of the apparatus, this is also due to the fact that not all people can identify their own needs, so that people simply trust the apparatus in their area. The approach used in this study is a qualitative approach. The qualitative research method is a method used to study the state of a particular subject, based on the philosophy of postpositivism (Sugiyono, 2016). The data collection method in this study was based on literature studies, observations, and interviews. Public services carried out in the Karanganyar Village have been running quite well and smoothly. In its implementation, there were still a few obstacles, but this was resolved properly and quickly by the apparatus. Lack of assistance from the central government, such as facilities and infrastructure, such as filing cabinets, which are felt to be lacking and the lack of an integrated system to facilitate apparatus services to the community. As well as the need for education and training for apparatus considering the times and increasingly advanced technology in order to support the creation of quality services.